Multicentre cohort study of cochlear implantation outcomes in Thailand - Patorn Piromchai (2022)
Objectives To report the status and outcomes of cochlear implantation in Thailand. Design Cohort study. Setting Tertiary care and university hospitals. Participants Patients who underwent cochlear implant surgery in Thailand. Interventions This project collected data from all government and university hospitals in Thailand where cochlear implant surgery was performed between 2016 and 2020. Primary and secondary outcome measures Baseline characteristics, operation data, complications, audiological outcomes and quality of life were reported. Results This study included 458 patients, and nearly half of the patients were children and adolescents (46.94%). The mean age of the patients was 2.96±5.83 years. At 1 year postoperatively, the mean pure tone average of the hearing threshold in the implanted ear significantly improved from unaided preoperative baseline (mean difference (MD) 64.23 dB HL; 95% CI 59.81 to 68.65; p<0.001). The mean speech recognition threshold also improved (MD 55.96 dB HL; 95% CI 49.50 to 62.42, p<0.001). The quality-of-life scores of the EQ-5D-5L, PedsQL and HUI3 questionnaires at 1 year showed improved mobility (range, 0-5; MD 0.65; 95% CI 0.05 to 1.25; p=0.037), hearing (range, 0-6; MD 0.96; 95% CI 0.30 to 1.61; p=0.006) and speech (range, 0-5; MD 0.44; 95% CI 0.04 to 0.84; p=0.031). Common complications included electrode dislodgement (2.18%), vertigo (1.23%) and meningitis (1.93%). Conclusions Excellent audiological outcomes and improvement in the quality of life in the mobility, hearing and speech domains were observed in patients who underwent cochlear implantation in Thailand.